BIOEKOLOGI MANGROVE DI DESA DASUN, KECAMATAN LASEM, KABUPATEN REMBANG, JAWA TENGAH - Efri Roziaty; Dela Rizki Utami (Bioscientiae, 2023)
Mangroves are one of the biotic components that make up ecosystems in coastal areas. The characteristics of mangroves are in the form of flowering plants with tree habitus  that are very tolerant of  high salt content. The ecosystem is a habitat for a variety of flora and fauna so it is known to have  high bioecology. The study analyzed the  bioecology of mangrove ecosystems in Dasun Village, Lasem District, Rembang Regency, Central Java.  The research method began with data collection using the random sampling method of quadratic transects with a size of 20 m x 20 m for  mangrove vegetation while for animals using an area approach with a radius of 10 m from the vegetation plot. Flora and fauna within the plot range and plot radius will be taken and recorded as mangrove ecosystem bioecological data. The sampling location was made as many as 3 different areas but still in one mangrove ecosystem area of Dasun Village, Lasem District. The results of the study found that there were 3 types of mangrove flora from three families, namely Primulaceae as many as 9 species, Combretaceae as many as 5 species and Rhizophoraceae as many as 171 species. The mangrove fauna found consists of 8 families of class Gastropoda, 2 families of class Malacostraca and 1 family of each class Pisces, Aves and Mammalia. The study also measured abiotic factors which include temperature, humidityn air, pH and salinity. The results of the study found temperatures ranging from 31.1 - 33.8 °C, air humidity 68 – 73 %, pH of 6.8 - 6.9 and salinity of 0.2 - 0.5 ppt. From these results, mangrove bioecology in Dasun Village shows the diversity of mangrove flora and fauna